Psycho-kinesitherapeutical Intervention Strategies for Increasing Posttraumatic Recovery Efficiency at Sports Performers - Claudia-Camelia, Burcea; Maria, Tudor; Iulian-Doru, Tudor (Procedia, social and behavioral sciences, 2013)
Planning the psycho-kinesitherapeutic intervention process in the knee recovery following ligament -plasty procedure in professional athletes is a dynamic process of follow-up of the plan achievement, developing the information obtained by prognosis and those having a feed-back type assess, each stage and recovery period by comparison to the objectives set, taking into consideration the way in which subjects respond to treatment. The positive effects of kinesitherapy influence beneficial ly the effects of other treatments as well (medication, psychological, ergotherapy) and vice versa, other types of treatments will have a favourable influence on kinesitherapy. The cognitive – behavioural therapy, together with the kinesic one, ensures the improvement of the psychical state and the disappearance of depression in these subjects. Kinesitherapy improves the Neuro- cognitive functions, having an anxiolytic effect. The success of the recovery depends on the teamwork (physician – kinesitherapist – psychologist – medical assistant) of the effective way of co-operation of the members of the recovery team.